AKIBAT HUKUM TERHADAP JABATAN NOTARIS YANG DINYATAKAN PAILIT BERDASARKAN UNDANG-UNDANG KEPAILITAN DAN UNDANG-UNDANG JABATAN NOTARIS (Analisa Kasus Menurut Putusan Nomor 20/Pdt.Sus-PKPU/PN.Niaga.Sby) - Vika, Rikna Lidya; Anggraini, Jum (PALAR (Pakuan Law review), 2024)
Abstract In the event that a court decision based on article 12 letter a of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notaries states that the Notary profession is declared bankrupt, then the Notary profession can be dishonorably dismissed. The provisions of this article and the provisions related to bankruptcy in the Law on Bankruptcy and Suspension of Debt Payment Obligations Number 37 of 2004 are contradictory, the object of bankruptcy and the legal consequences of bankruptcy. Bankruptcy is of course very detrimental because it is given the sanction of dishonorable dismissal. In this research, the problem raised is how to regulate the position of a notary who has been bankrupted based on the notary position law and the bankruptcy law for notaries who have been bankrupted based on Decision Number 20/PDT.SUS-PKPU/2020/PN.Niaga. Sby and what is the legal protection for notary positions that are bankrupted based on the Law on Notary positions and Bankruptcy based on Decision Number 20/PDT.SUS- PKPU/2020/PN.Niaga. Sby. To answer these problems, normative juridical reseach method is ussed by secondary data. From the research results, it can be concluded that a Notary can be declared bankrupt based on a commercial court decision which has permanent legal force (inkrach). As regulated in 12 UUJN-P, a Notary who is declared bankrupt, apart from losing his right to manage and manage assets as a result of a bankruptcy petition being filed, the Notary is also dishonorably dismissed by the Minister of Law and Human Rights on the basis of a proposal from the Notary's MPP. That legal protection for notaries who discharged from their position (employment) due to bancruptcy has been blurring legal norms and followed by legal norms emptiness in notary position law and Regulations of the Ministry of Law and Human Rights Number 25 of 2014 concerning Requirements and Procedures for Appointment, Transfer, Dismissal and Extension of the Notary's Term of Office. Keywords: Notary, Bankruptcy, notary termination. Abstrak Pasal 12 huruf a Undang-Undang Nomor 2 Tahun 2014 tentang Perubahan Atas Undang-Undang Nomor 30 Tahun 2004 tentang Jabatan Notaris, jika putusan pengadilan menyatakan bahwa profesi Notaris dinyatakan pailit, maka profesi Notaris tersebut dapat diberhentikan secara tidak hormat. Ketentuan pasal ini dan ketentuan terkait kepailitan dalam Undang-Undang Kepailitan dan Penundaan Kewajiban Pembayaran Utang Nomor 37 Tahun 2004 bertentangan, objek pailit serta akibat hukum dari kepailitan, Kepailitan tentu saja sangat merugikan karena diberikan sanksi diberhentikan dengan tidak hormat. Dalam penelitian ini permasalahan yang diangkat.Bagaimana pengaturan terhadap jabatan notaris yang dipailitkan berdasarkan undang-undang jabatan notaris dan undang-undang kepailitan terhadap notaris yang di pailitkan berdasakan Putusan Nomor 20/PDT.SUS-PKPU/2020/PN.Niaga.Sby dan Bagaimana Perlindungan Hukum Terhadap jabatan Notaris yang dipailitiakan berdasarkan Undang-Undang jabatan Notaris dan Kepailitan berdasakan Putusan Nomor 20/PDT.SUS-PKPU/2020/PN.Niaga. Sby. Untuk menjawab permasalahan tersebut digunakan metode penelitian yuridis normatif dengan mengumpulkan data sekunder. Berdasarkan hasil penelitian dapat di simpulkan Bahwa Notaris dapat dinyatakan pailit berdasarkan putusan pengadilan niaga hukum yang bersifat tetap (inkrach). Dalam Pasal 12, Notaris yang dinyatakan pailit, selain kehilangan haknya untuk mengurus dan mengatur harta kekayaan sebagai akibat dari permohonan kepailitan yang diajukan, Notaris juga diberhentikan dengan tidak hormat oleh Menkumham atas dasar usulan dari MPP Notaris.Bahwa Perlindungan hukum bagi notaris yang di berhentikan dari jabatannya akibat pailit yaitu telah terjadi kekaburan norma hukum dan diikuti kekosongan norma hukum dalam Undang-Undang Jabatan Notaris dan Peraturan Kementerian Hukum dan Hak Asasi Manusia Nomor 25 Tahun 2014 tentang Syarat dan Tata Cara Pengangkatan, Pengalihan, Pemberhentian, dan Perpanjangan Masa Jabatan Notaris. Kata kunci: Notaris, Pailit, Pemberhentian tidak hormat.